COMPARATIVE STUDY OF THE STUDENTS’ MATH LEARNING OUTCOMES TAUGHT USING TYPE OF COOPERATIVE LEARNING METHOD NUMBERED HEAD TOGETHER (NHT) AND GAMES TEAM TOURNAMENT (TGT) TO STUDENTS CLASS VII SMPN 1BAULA - Supratman Supratman (JME (Journal of Mathematics Education), 2016)
The problems in this research are: (1) What is the result of learning mathematics in grade VII SMP Negeri 1 Baula taught by type of cooperative methods Numbered Heads Together (NHT)? (2) What is the result of learning mathematics in grade VII SMP Negeri 1 Baula taught by type of cooperative methods Team Games Tournament (TGT)? (3) Are the results of students' mathematics learning kelasVII SMP Negeri 1 Baula taught by cooperative methods with NHT is different with students who are taught by the type cooperative method TGT? The hypothesis in this study are: the results of students' mathematics learning class VII SMP Negeri 1 Baula taught by  cooperative methods NHT type is  different with the students taught with methods TGT. The population in this study was all students of class VII SMP Negeri 1 Baula in the second semester of the 2011/2012 academic year.  Samples taken as many as two classes, namely class VIIc and VIId class. The results showed: (1) The results of students' mathematics learning of class VIIc are taught using cooperative learning NHT type obtained an average value of student learning outcomes at 82.86 and the passing rate of 100%. (2) Results of mathematics learning of class VIId taught using methods TGT obtained average value result of 67.25 and the percentage of students passing rate at 80%. (3) The results of hypothesis test obtained tcount ttable or equal to 3.997 2.02 with df = 39 at significance level α = 0.05. Thus, it can be concluded that there were significant differences in the results of students' mathematics learning that are taught using NHT and IGT methods in the seventh grade students of SMP Negeri 1Baula.